2015
DOI: 10.1371/journal.pone.0123544
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Glycolytic Enzymes as Therapeutic Targets in the Treatment of Glioblastoma

Abstract: Major efforts have been put in anti-angiogenic treatment for glioblastoma (GBM), an aggressive and highly vascularized brain tumor with dismal prognosis. However clinical outcome with anti-angiogenic agents has been disappointing and tumors quickly develop escape mechanisms. In preclinical GBM models we have recently shown that bevacizumab, a blocking antibody against vascular endothelial growth factor, induces hypoxia in treated tumors, which is accompanied by increased glycolytic activity and tumor invasiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 45 publications
2
92
0
Order By: Relevance
“…In renal cell carcinoma, ENO2 was not found to affect tumor growth [24]. However, another recent study has shown a correlation in glioblastomas between increased ENO2 expression and tumor progression in vivo [25]. Further studies will be required to determine the role of ENO2 in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…In renal cell carcinoma, ENO2 was not found to affect tumor growth [24]. However, another recent study has shown a correlation in glioblastomas between increased ENO2 expression and tumor progression in vivo [25]. Further studies will be required to determine the role of ENO2 in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…A glycolytic metabolism is highly correlated with tumor proliferation. Knockdown or pharmacological inhibition of glycolytic enzymes reduces growth in a variety of cancers . Forced induction of respiration has led to slower growth rates both in vitro and in vivo .…”
Section: Glycolysis Reduces Overabundant Ros To Increase Survival Andmentioning
confidence: 99%
“…Knockdown or pharmacological inhibition of glycolytic enzymes reduces growth in a variety of cancers. [50][51][52][53] Forced induction of respiration has led to slower growth rates both in vitro and in vivo. 6,54,55 Conversely, lower oxidative phosphorylation due to mutant mitochondria increases both glycolysis and growth.…”
Section: Glycolysis Reduces Overabundant Ros To Increase Survival Andmentioning
confidence: 99%
“…PGAM1 is an enzyme participating in glycolysis by converting 3‐PG (3‐phosphoglycerate) to 2‐PG (Fothergill‐Gilmore & Watson, ) whose expression also correlates with glioma grade and patient survival (Gao et al, ). Although its role in cancer is still poorly understood, its knockdown increases the survival of glioblastoma bearing mice (Sanzey et al, ). PGAM1 downregulation appeared thus as an interesting possible event triggered by CM16 to combat glioma.…”
Section: Discussionmentioning
confidence: 99%